Practice report: How Can the Audio Description of Screen Adaptations Benefit from Literary Works? A Pedagogical Proposal Illustrated by The Queen’s Gambit - Igareda, Paula (Journal of Audiovisual Translation, 2025)
This report presents a pedagogical proposal for trainers to lead an in-class exercise with trainee audio describers to support students in source text analysis, understanding film narrative, and its transposition into audio description. It uses the novel The Queen’s Gambit (Tevis, 1983) and its adaptation (Frank, 2020) together with its English and German ADs to propose the literary text as an important source, along with the audiovisual one, for the text analysis (understanding the plot, pacing and timing, character development), terminology and narrative cohesion. This approach can be used as a pedagogical resource for training future AD professionals, working with disciplines that complement each other and create new synergies with satisfactory results, such as literature, screen adaptation, audiovisual translation, and media accessibility. Lay summary This report proposes a teaching method for training students to become audio describers, the professionals who create spoken descriptions of visual media for people with visual impairments. The method involves having students analyze both a novel, The Queen's Gambit, and its screen adaptation, using both the original text and the audio descriptions in English and German. The exercise helps students understand key aspects of the story, such as plot, timing, and character development, and learn the right language and terms to use for audio descriptions. By combining elements of literature, film, translation, and media accessibility, this approach creates a valuable resource for training future audio describers, offering effective ways to bridge these different fields.